2012
DOI: 10.1007/s00332-012-9158-x
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Framework for Critical Transitions: Normal Forms, Variance and Applications

Abstract: Critical transitions occur in a wide variety of applications including mathematical biology, climate change, human physiology and economics. Therefore it is highly desirable to find earlywarning signs. We show that it is possible to classify critical transitions by using bifurcation theory and normal forms in the singular limit. Based on this elementary classification, we analyze stochastic fluctuations and calculate scaling laws of the variance of stochastic sample paths near critical transitions for fast sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(166 citation statements)
references
References 97 publications
8
158
0
Order By: Relevance
“…S8. Previous studies have shown that CSD indicators change smoothly before bifurcation points (8,41). We confirmed smooth changes in CV and AR1 in our mutualistic communities under a gradual decline of mutualistic strength (Fig.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…S8. Previous studies have shown that CSD indicators change smoothly before bifurcation points (8,41). We confirmed smooth changes in CV and AR1 in our mutualistic communities under a gradual decline of mutualistic strength (Fig.…”
Section: Methodssupporting
confidence: 74%
“…This phenomenon of "critical slowing down" appears to be generic for a wide class of local bifurcations (8), at which the current equilibrium state of a system loses stability before being replaced by another equilibrium state. Critical slowing down may be captured by two simple statistical signals in the dynamics of complex systems (6): increasing variance and rising correlation.…”
mentioning
confidence: 99%
“…It is expected to be of particular relevance when a slow change in some external parameter which drives the system towards the bifurcation point. In this case transitions are called critical transitions and the mathematical framework used comes from dynamical systems theory [4,5,6]. This method is pertinent to systems that are dynamically effectively low dimensional in which the transition takes the form of a bifurcation captured by a robust macroscopic variable, which emerges from the micro dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from a well studied tritrophic food chain model [37], we investigate the disease controllability aspects of allochthonous inputs in this paper. The bifurcation phenomena of the model are analysed with respect to important biological parameters for finding periodic and other behaviours [42] of the model.…”
Section: Introductionmentioning
confidence: 99%